2016
DOI: 10.1111/pace.12878
|View full text |Cite
|
Sign up to set email alerts
|

Implantable Cardioverter Defibrillator Outcomes in Pediatric and Congenital Heart Disease: Time to System Revision

Abstract: The need for ICD system revision is high in this pediatric and CHD population and occurs at a rate similar to the rate of receiving appropriate therapy. These results highlight the need for judicious implant criteria and improved device longevity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 13 publications
3
25
0
Order By: Relevance
“…In leads with only CCE, the indications for extraction were structural failure in one (5%) and elective extraction for advisory in one (5%) lead. 1,2,[7][8][9] In contrast to the higher rate of electrical failure, the 16% rate of CCE seen in our cohort is in keeping with previously reported rates of CCE in adult patients. A recent study of 3763 Riata leads found a cumulative incidence of electrical failure of 5.2% at 8 years, while a recent meta-analysis found an overall electrical failure rate of 6.3%.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…In leads with only CCE, the indications for extraction were structural failure in one (5%) and elective extraction for advisory in one (5%) lead. 1,2,[7][8][9] In contrast to the higher rate of electrical failure, the 16% rate of CCE seen in our cohort is in keeping with previously reported rates of CCE in adult patients. A recent study of 3763 Riata leads found a cumulative incidence of electrical failure of 5.2% at 8 years, while a recent meta-analysis found an overall electrical failure rate of 6.3%.…”
Section: Resultssupporting
confidence: 92%
“…Electrical failure was the indication for lead extraction in 12 (57%) leads, with five of these leads having concomitant CCE. 1,2,[7][8][9] This finding may be related to the Riata lead being more susceptible to the factors influencing lead failure in children and patients with CHD, including lead stress related to somatic growth and higher activity levels. In leads without structural or electrical The rate of Riata electrical failure, reported at 43% in this study, is much higher than what has been reported to date in predominantly adult patients.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…While the use of an implantable cardioverter-defibrillator (ICD) can be life-saving, it also has the potential to cause significant morbidity, both medically and psychosocially. [1][2][3] As such, current research is examining predictors of SCD to help clinicians select those patients most likely to benefit from primary preventive ICD placement. Furthermore, though ICD placement can be a life-saving primary prevention option, because of factors inherent to the pediatric population, careful thought must be given to the specific indications for device placement in each child.…”
Section: Introductionmentioning
confidence: 99%